Self-healing and easy-to-shape mineralized hydrogels for iontronics. Issue 27 (16th June 2020) - Cao, Jinfeng; Kang, Yanhui; Wu, Xiaoqing; He, Chen; Zhou, Jinping
Abstract : Self-healing and easy-to-shape mineralized hydrogels for iontronics were fabricated through physically cross-linked PVP and CaCO3 . Abstract : Hydrogel-based multifunctional materials have attracted much attention. In this work, novel mineralized hydrogels were fabricated through physically cross-linked polyvinylpyrrolidone (PVP) and CaCO3 . The mineralized hydrogels were prepared by simply mixing CaCl2, Na2 CO3, and PVP in aqueous solutions. The CO3 2− induced the aggregation of the PVP chains and the CaCO3 particles in situ generated in the aqueous solution worked as fillers to strengthen the hydrogels. Based on this method, other kinds of mineralized hydrogels were prepared by replacing the Ca 2+ with different metal ions. The mineralized hydrogels displayed shapeable, self-healing and thixotropic properties. Moreover, the mineralized hydrogel-based sensor showed good and stable sensitivity to compressive pressure, and could be used to monitor human actions. This work presents a facile method for preparing mineralized hydrogels, which are promising for various applications due to their outstanding properties.